2020
DOI: 10.3390/su12145623
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Regular Use of Ridesourcing and Walking Mode Choice in Cairo and Tehran

Abstract: The rapid adoption of ridesourcing poses challenges for researchers and policymakers in the Middle East and North Africa (MENA), as it is an evolving new transport mode, and there is little research explaining its effects on mobility behaviors in this region. There is a concern that ridesourcing, which offers convenient and relatively cheap door to door services, encourages citizens to replace their sustainable travel modes, like walking, with car use. This effect has been studied relatively well in metropolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Other car-sharing studies, like those of Efthymiou et al (2013) and Wang et al (2012), also found negative coefficients for the age attributes in their regression models [23,28]. Moreover, this finding is in the same direction of another study in the field of the online ride-hailing in Cairo, which indicates that more younger people have adopted this ICT-based mobility mode than older people in Cairo [14,49].…”
Section: Blr Modelsupporting
confidence: 56%
See 1 more Smart Citation
“…Other car-sharing studies, like those of Efthymiou et al (2013) and Wang et al (2012), also found negative coefficients for the age attributes in their regression models [23,28]. Moreover, this finding is in the same direction of another study in the field of the online ride-hailing in Cairo, which indicates that more younger people have adopted this ICT-based mobility mode than older people in Cairo [14,49].…”
Section: Blr Modelsupporting
confidence: 56%
“…The respondent's main mode of transportation has a very highly significant negative coefficient if it is public transportation or physical modes, like walking or biking. This reassures the concerns of those who think that car-sharing would replace the other sustainable mobility modes [49]. The reason for public transport's negative coefficient is clear, as it is by far the most dominant means of transport [47], and a large segment of the population cannot afford another mode, as it is the cheapest mode of motorized transportation in the GCMA [53].…”
Section: Effects Of Trip Variablesmentioning
confidence: 68%
“…However, there is little research on whether ridesourcing has positive or negative impacts on the sustainability of urban transport in the MENA region. The evaluation of ridesourcing as a sustainable or unsustainable transport mode depends on whether it supports or replaces other sustainable modes like public transport and nonmotorized modes [17,76]. This paper tried to give an insight into the relationship between ridesourcing adaptation and the frequency of public transport use in two cities of the MENA region.…”
Section: Discussionmentioning
confidence: 99%
“…The interviewees imagined a manipulated situation to answer this type of question. Some studies applied other approaches to understand how the tendency of frequent ridesourcing users is toward nonmotorized modes [81,82] and public transport mode [83] by asking a think-forward question from regular users of ridesourcing in the present tense like "how often do you make travels by nonmotorized modes/public transport? ".…”
Section: Ridesourcing Services and Mobility Behaviorsmentioning
confidence: 99%